Hubungan Paritas, Jarak Kehamilan dan Riwayat Penyakit dengan Kejadian Kekurangan Energi Kronik (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Makrayu Palembang tahun 2022 - Erita, Melli; Amlah, Amlah; Rahmawati, Eka (NHM PRESS, 2023)
Chronic Energy Deficiency (CED) among pregnant women is characterized by an upper arm circumference of less than 23.5 cm, hemoglobin levels below 11g% in the first and third trimesters, and abnormal weight gain in the second and third trimesters. During pregnancy, it is recommended that maternal nutrition improves, resulting in a weekly weight gain of 0.5 kg. This study aims to find out the relationship between parity, pregnancy spacing, medical history, and the incidence of chronic energy deficiency among pregnant women at Makrayu Community Health Center, Palembang, in 2022. This study employed a quantitative approach and analytical survey method with a Cross-Sectional design, where both independent and dependent variables were collected simultaneously using secondary data. The population consisted of 105 individuals, and the sample was drawn using total sampling, with 105 respondents participating. The results of univariate and bivariate analyses among the 105 respondents revealed that 27.6% of mothers experienced CED, 42.9% had risky parity, 48.6% had risky pregnancy spacing, and 56.2% had a medical history. Bivariate analysis showed that the p-values for parity, pregnancy spacing, and medical history were 0.007, 0.018, and 0.022, respectively, all of which were ≤ 0.05. This showed a significant relationship of parity, pregnancy spacing (ρ value= 0.018), and medical history (ρ value= 0.022) with the Chronic Energy Deficiency. In conclusion, there was a simultaneous relationship of parity, pregnancy spacing, and medical history with the incidence of chronic energy deficiency at Makrayu Community Health Center, Palembang, in 2022. It is recommended that the Community Health Center improve its services for pregnant women to prevent Chronic Energy Deficiency (CED), which can lead to maternal and infant mortality.